VP100 Ultraradical Ovarian Cancer Surgery Comparative Clinical Effectiveness. (2019) - Cummins, Carole; Patrick, Hannah; Long, Joanna; Kumar, Satyam; Sundar, Sudha; Bramley, George
Abstract : Introduction: Ovarian Cancer is usually diagnosed at an advanced stage. Extensive or ultra-radical surgery aims to improve the outcome by removing all visible tumour. National Institute for Health and Care Excellence UK 2013 Guidance expressed concern about its efficacy and safety, recommending research comparing complication rates, survival and quality of life with those following standard surgery. We present prospective observational data on quality of life and survival following surgery for advanced ovarian cancer. Innovative methods were used to collect patient reported outcomes and complex surgical information to compare outcomes of surgery of greater or lesser complexity used in routine practice. Methods: A cohort study collected disease, surgical, complications, survival and quality of life data (validated instruments including EURO-QOL, EORTC-30 and OVA28) across a 2-year period in 12 United Kingdom sites and in parallel studies in Melbourne, Australia and Kolkata, India. Results: Two hundred and sixty patients undergoing cytoreductive surgery were recruited in 12 months. Centres varied in utilisation of complex surgical procedures. Excluding patients with inoperable disease, 125 patients underwent low, 70 intermediate and 63 high Surgical Complexity Score (SCS) procedures. Complete cytoreduction with < 1cm residual disease was achieved in 100/125 (80 percent) low, 65/70 (92 percent) intermediate, and 57/63 (90 percent) high SCS groups (p = 0.023). Compliance with 12 months questionnaires was 89%. All surgical groups had improved EORTC QLC 30 Global at 12 months compared with prior to operation, with overlapping 95% confidence intervals and no between group differences at 12 months. Complications, survival and quality of life adjusted for disease burden and surgical complexity over 2 years' follow-up will be described. Conclusions: Results will inform the update of NICE Interventional Procedures guidance recommendations on clinical governance arrangements for ovarian cancer surgery and enable clinicians and patients to better understand the outcomes of surgery, informing the consent process.